The role of doctors in smoking cessation: evidence from the Cochrane Library - Lancaster, Tim (SA Heart Journal, 2017)
This article examines the role of doctors in assisting patients who smoke to quit, using evidence from Cochrane systematic reviews of randomised trials. Doctors may help such patients by providing advice, referring patients for counselling and support and by offering pharmacological therapy. Complementary therapies used for smoking cessation include hypnotherapy and acupuncture, but there is a lack of evidence that these interventions have a specific effect in aiding cessation. The number needed to treat (NNT) for simple advice to unselected smokers is 50 - 120. Based on a median no-treatment clinical trial quit rate of 7.5%, the NNT for nicotine replacement therapy is 23 (95% CI 20 to 27), for the antidepressant Bupropion 18 (95% CI 14 to 23), and for the nicotinic partial agonist Varenicline 10 (95% CI 7 to 14). These numbers compare favourably with other preventive healthcare interventions. There remains wide variations in the extent to which these interventions are available in different healthcare systems.